Efeitos da interação de plasma na absorção ótica em super-rede randômica de pontos quânticos. - Abreu, Eduardo de Paula (2004)
In this work the ground and first excited states of the electron are calculated in interacting one-dimensional, two-dimensional lattices and multilayers of cylindrical quantum dots containing at the most an electron and considering both infinite and finite potential barriers. The dimensions and the occupation of the quantum dots are chosen randomly using Monte Carlo s method. In the case of finite barrier we calculated the levels of energy through the Density Functional Theory (DFT ). We calculated the envelope function considering the eﬀective mass approximation and using the numeric method developed by Samita Gangopadhyay and B.R. Nag. Once obtained the levels of energy, we calculated the absorption coeﬃcient considering the electron-electron interaction. The calculations show the influence of the plasma interaction in the absorption. The results demonstrate a change of the absorption coeﬃcient as a function of the density of quantum dots. When the electric field is applied the absorption peak moves to the right indicating a collective response of interacting localized electrons.